Reinforce Students’ Motivation in Learning Recount Text through Subtitled Animation Video - Imroati Istibsyaroh Ar Ruhimat (FKIP e-PROCEEDING, 2017)
Abstract: The use of interesting media seems promising in reinforcing the students’ motivation in participating the learning activity in the classroom. Subtitled animation video as one of media which is often considered to be used in learning activity because it provides a realistic representation of the material in the classroom. Hence, a sequence of learning activity was conducted in learning recount text in which subtitled animation video was used as the teaching and learning media. This paper presents some sub topics deal with the introduction, related literatures review including students’ motivation in learning process and the use of subtitled animation video in learning recount text, discussion which covers how the activity was done and resulted and the last is conclusion. Key words: recount text, subtitled animation video, students’ motivation